Erratum on the article ‘Comments on “multiple criteria decision making (MCDM) methods in economics”: an overview’ (DOI: 10.3846/20294913.2012.753489) - Liou, James J. H.; Tzeng, Gwo-Hshiung (Technological and Economic Development of Economy, 2013)
"Erratum on the article ‘Comments on “multiple criteria decision making (MCDM) methods in economics”: an overview’ (DOI: 10.3846/20294913.2012.753489). " Technological and Economic Development of Economy, 19(1), p Ia-Ib First published online: 14 Mar 2013